2020
DOI: 10.2147/rmhp.s242724
|View full text |Cite
|
Sign up to set email alerts
|

<p>To What Extent Do Ecological Factors of Behavior Contribute to the Compliance of the Antenatal Care Program in Dumai City, Indonesia?</p>

Abstract: Purpose: Maternal mortality rate (MMR) in Indonesia is still relatively high, at 305 per 100.000 live births (2015). Routine visit to antenatal care is the best way to reduce MMR. Inspite of this, the number of antenatal care visits among pregnant women is still low. This study aimed to measure the influence of behavioral ecological factors with the compliance of pregnant women to visit antenatal care. Patients and Methods: Study population was pregnant women living in Dumai City, Indonesia. This study was a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…According to Patel's (2016) research, higher levels of education are associated with better knowledge, which can help in the selection of relevant information to support that knowledge. This statement is in line with the research conducted by Ismainar et al (2020), which suggests that education and knowledge levels influence the mindset that contributes to compliance with antenatal care. Age is also a factor that influences a person's knowledge, and the research results indicate that the majority of respondents were between the ages of 24-30 years (early adulthood) (60.0%).…”
Section: Resultssupporting
confidence: 88%
“…According to Patel's (2016) research, higher levels of education are associated with better knowledge, which can help in the selection of relevant information to support that knowledge. This statement is in line with the research conducted by Ismainar et al (2020), which suggests that education and knowledge levels influence the mindset that contributes to compliance with antenatal care. Age is also a factor that influences a person's knowledge, and the research results indicate that the majority of respondents were between the ages of 24-30 years (early adulthood) (60.0%).…”
Section: Resultssupporting
confidence: 88%
“…These causes reflect the acuteness of this disease. In Pakistan, most of studies have been conducted on anemia/iron deficiency on growing children and females in different areas (10) . This study was conducted to evaluate the causes of Deficiency of iron anemia to provide better treatment and to reduce the morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in view of all above facts and severances of this medical condition during pregnancy more research is need of time in developing countries like Pakistan.In Pakistan, Deficiency of iron is the most common cause of anemia and mostly observed in pregnant women (12) . Different studies regarding to IDA have been conducted in different areas of Pakistan to examined/evaluate the frequency of this main health related disease (8,10) . This retrospective study was conducted to evaluate the frequency of IDA to maintain a better treatment and to reduce the death ratio and to improve quality of life of patients affected by anemia.…”
Section: Introductionmentioning
confidence: 99%
“…The factors that influence pregnant women's adherence in attending pregnant women's classes are knowledge, a distance of residence, family support (husband/parents/in-laws), and parity. Going along with it, (Ismailar et al2020) concluded that five dominant variables influence a person's adherence to health services: knowledge, cultural beliefs, family support, friend support, and health facilities (Ismainar et al, 2020). The factors that most influence pregnant women's compliance in participating in the class program for pregnant women in Aceh Besar District.…”
Section: The Variables That Most Influence Internal Factors and Exter...mentioning
confidence: 99%